The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jafc.0c03310
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Attenuates Hepatic Fat Accumulation via Activating Mitochondrial Biogenesis and Autophagy through the AMPK Pathway

Abstract: Two experiments were carried out to examine the impacts of hydroxytyrosol (HT) on lipid metabolism and mitochondrial function in Megalobrama amblycephala. Triplicate groups of fish were fed four test diets: (1) low-fat diet (LFD, 5% fat), (2) high-fat diet (HFD, 15% fat), (3) LFD + 100 mg/kg HT (LFD + HT), and (4) HFD + 100 mg/kg HT (HFD + HT) (in vivo). Hepatocytes from the same batch were exposed to three media including L-15 medium (L15), oleic acid (OA) medium [L15 + 400 μM OA], and OA + HT medium [L15 + 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
(82 reference statements)
2
30
1
Order By: Relevance
“…Similar to some previous studies, fish-fed HFD showed poor growth, excess fat deposition, and increased transaminase activities (Dong et al, 2020;Yin et al, 2021). QUE supplementation mitigated the decreasing growth performance and excess fat deposition, which is in agreement with previous studies (Jia et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to some previous studies, fish-fed HFD showed poor growth, excess fat deposition, and increased transaminase activities (Dong et al, 2020;Yin et al, 2021). QUE supplementation mitigated the decreasing growth performance and excess fat deposition, which is in agreement with previous studies (Jia et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Further, there is crosstalk and/or interaction between mitochondrial damage and ERS. Based on the above, more researchers suggest that the therapies acting on mitochondria and ER are novel strategies for the prevention and protection against excess fat deposition (Wang et al, 2018;Dong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a transcriptional activator of the nuclear receptor family, PGC-1α is the transcriptional activator of PPAR-γ, both of which regulate the expression of genes related to energy metabolism (Di et al, 2018). PGC-1α, which mainly regulates mitochondrial production and the homeostasis of mitochondrial copy number, is the main regulator of mitochondrial production downstream in the AMPK pathway (Dong et al, 2020). It regulates the dynamic balance between mitochondrial function and the energy produced, activates the antioxidant enzyme system, and scavenges ROS (Suntar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Protein homogenates preparation from turbot liver and hepatocytes, and western blotting were processed as refer to previous studies ( 27 , 28 ). Equal amounts (30 μg per lane) of protein were separated by sodium dodecyl sulfate-polyacrylamide gels (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%